2016
DOI: 10.14414/jebav.v19i2.568
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and consequences of transfer of training in public sector organizations

Abstract: A B S T R A C T

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
(44 reference statements)
1
2
0
Order By: Relevance
“…The results of this study support the opinions of Bawono and Purnomo (2016). The results of his research show that supervisor support (supervisor support) has a significant effect on the transfer of training.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The results of this study support the opinions of Bawono and Purnomo (2016). The results of his research show that supervisor support (supervisor support) has a significant effect on the transfer of training.…”
Section: Resultssupporting
confidence: 85%
“…From the previous research study found differences in the results of research conclusions regarding the role of supervisor support for training transfers. Bawono and Purnomo (2016) argue that supervisor support has a positive and significant effect on training transfer, while in another study conducted by Maung and Chemsripong (2014) stated that supervisor support did not significantly influence training transfers.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation